THE EKSPLORASI KEBUTUHAN PASIEN HIPERTENSI PADA WILAYAH URBAN KABUPATEN JEMBER : EKSPLORASI KEBUTUHAN PASIEN HIPERTENSI PADA WILAYAH URBAN KABUPATEN JEMBER - Achmad Sya’id; Hella Meldy Tursina; M.Elyas Arif Buidman (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Hypertension or commonly called the silent killer is a disease that has unclear signs and symptoms with blood pressure conditions that exceed normal limits and can pose a risk to the heart, kidneys and brain. Hypertension that does not get good treatment causes complications such as stroke, coronary heart disease, diabetes, kidney failure and blindness. The purpose of this study was to gain an in-depth understanding of the needs of hypertensive patients. This study uses a descriptive phenomenological design. Data collection was done by in-depth interviews. Participants in this study were hypertensive patients. The data collected is recorded conversations made verbatim transcripts and analyzed using the Open Code 4.0 application. The results of this study identified 3 research themes related to the needs of hypertensive patients, namely the need for emotional support. The existence of direct expressions regarding the expected needs of hypertensive patients is one form of support so that the management of hypertension care can run well. The management of hypertension that is carried out properly is expected that hypertensive patients can maintain the stability of hypertension pressure.